2007
DOI: 10.1021/nl072563f
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Porphyrin Polymers in Solution and at the Solid−Liquid Interface

Abstract: We have investigated in detail the self-assembly of a chiral porphyrin trimer in different solvents and correlated this behavior to the aggregation of the molecule at a solid-liquid interface. In n-hexane and cyclohexane, CD spectroscopy and dynamic and static light scattering studies showed that the porphyrin trimer self-assembles already at micromolar concentrations into long, chiral supramolecular polymers, which precipitate as fibers when the solution is drop-cast onto a mica surface. In contrast, in chlor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
89
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 99 publications
(92 citation statements)
references
References 25 publications
3
89
0
Order By: Relevance
“…12 The achiral porphyrin trimer 1 self-assembles into a racemate 55 of P-and M-helical stacks, whereas the chiral enantiopure trimer 2 yields stacks with one helical sense. 13 Scanning tunneling microscopy (STM) and Atomic force microscopy (AFM) revealed that when micromolar solutions of these compounds in chloroform were dropcasted onto a mica 60 surface, extended patterns of equidistant single columnar stacks of molecules were obtained, which formed spontaneously as a result of a fine balance between molecular self-assembly and dewetting. 11 In more apolar solvents like nhexane or cyclohexane, self-assembly of the trimers appeared to be much stronger, resulting in the formation of stacks in solution already at very low concentrations (< 10 -8 M).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…12 The achiral porphyrin trimer 1 self-assembles into a racemate 55 of P-and M-helical stacks, whereas the chiral enantiopure trimer 2 yields stacks with one helical sense. 13 Scanning tunneling microscopy (STM) and Atomic force microscopy (AFM) revealed that when micromolar solutions of these compounds in chloroform were dropcasted onto a mica 60 surface, extended patterns of equidistant single columnar stacks of molecules were obtained, which formed spontaneously as a result of a fine balance between molecular self-assembly and dewetting. 11 In more apolar solvents like nhexane or cyclohexane, self-assembly of the trimers appeared to be much stronger, resulting in the formation of stacks in solution already at very low concentrations (< 10 -8 M).…”
mentioning
confidence: 99%
“…In that case, the assemblies are not in equilibrium with the monomeric building blocks, 12 and dropcasting of their solutions onto mica gave irregular networks of fibers with the 70 width of a single molecule and lengths in the order of micrometers. 13 Here we study in detail the aggregation behaviour of porphyrin trimers 1 and 2 based on BTA in different solvents and with various techniques, including nuclear magnetic 75 resonance (NMR), Fourier-transform infrared (FT-IR) spectroscopy, ultraviolet-visible (UV-vis) light spectroscopy, circular dichroism (CD), and small angle neutron scattering (SANS). We report on the shape and size of the assemblies under various conditions, and on the hierarchical assembly of 80 the columnar stacks of porphyrin trimers into networks that gelate the solvent.…”
mentioning
confidence: 99%
“…Recently porphyrins have more interest to be examined after known that size of the molecules in nanometer orde [5][6][7][8]. Porphyrin supramolecular structures can be formed on metal substrate surfaces as a result of metal-porphyrin and porphyrin-porphyrin interactions [9]. As such, individual molecules can be considered as single nanometer devices [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…A Recent paper reported that porphyrin molecule size of the order of nanometers. Furthermore, porphyrin molecules can be formed into supramolecular [2] and can also be formed into nanoring [3] so that potentially as molecular device [5].…”
Section: Introductionmentioning
confidence: 99%